2021
DOI: 10.9745/ghsp-d-20-00578
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Landscape of Medical Device Regulation in East, Central, and Southern Africa

Abstract: Although 11 of 14 member countries of the College of Surgeons of East, Central, and Southern Africa have legislation mandating the regulation of medical devices, only half are currently developing medical device regulatory processes and half do not have a formal process. n A country's gross domestic product had a strong correlation to level of medical device regulation. n The number of years that had elapsed from the country's independence to the present had a strong correlation to the status of the country's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(57 citation statements)
references
References 24 publications
(31 reference statements)
4
52
1
Order By: Relevance
“…Participants in the focus group discussion were selected through purposive sampling. Through literature ( 1 , 2 , 9 ) and knowledge of the local regulatory bodies in Uganda, the researchers enlisted key departments in the bodies that participated specifically in medical device regulation. Department heads and representatives were formally invited to the discussion through their supervisors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants in the focus group discussion were selected through purposive sampling. Through literature ( 1 , 2 , 9 ) and knowledge of the local regulatory bodies in Uganda, the researchers enlisted key departments in the bodies that participated specifically in medical device regulation. Department heads and representatives were formally invited to the discussion through their supervisors.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the medical device regulations 2017/745 of the European union provide for a four-class risk classification scheme for medical devices, a Conformité Européenne (CE) marking requirement, and a system of notified bodies to regulate safety and marketing of medical devices ( 6 ). Conversely, medical device regulation in developing countries, especially in Africa, is not well developed and is characterized by high degrees of variability and irregularity ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RECs could expand their inclusion criteria to include a varied technical expertise such as biomedical engineers since there is a strong biomedical engineering program at local universities such as Makerere University ( 17 , 20 , 21 ). In addition to developing a formalised framework, biomedical entities, such as universities, should reach out to RECSs to provide access to appropriate expertise as needed which diversify the board's expertise to holistically evaluate applications not only from the clinical perspective, but also from a technical feasibility and design quality perspective ( 25 ) as biomedical engineers are trained to do.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organisation (WHO), a clear and robust regulatory framework is necessary to guarantee public health, safety, and performance of imported medical devices and those locally manufactured ( 24 ). Although there is a presence of national regulatory bodies for medicines and health products in most African countries ( 25 ), a review of regulatory bodies for ten African countries including Uganda ( 26 ), found that these bodies are primarily concerned with regulation of imported medical devices and medicines, as opposed to locally made devices. The National Drug Authority (NDA), a Ugandan regulatory body for example, has elaborate guidelines for introducing new locally manufactured pharmaceutical products onto the market that detail requirements for production, testing, packaging, and licensing ( 27 ).…”
Section: Introductionmentioning
confidence: 99%